Spatio-temporal Distribution of Suicide Risk in Iran: A Bayesian Hierarchical Analysis of Repeated Cross-sectional Data - Seyed Saeed Hashemi Nazari; Kamyar Mansori; Hajar Nazari Kangavari; Ahmad Shojaei; Shahram Arsang-Jang (Korean Society for Preventive Medicine, 2022)
Objectives We aimed to estimate the space-time distribution of the risk of suicide mortality in Iran from 2006 to 2016. Methods In this repeated cross-sectional study, the age-standardized risk of suicide mortality from 2006 to 2016 was determined. To estimate the cumulative and temporal risk, the Besag, York, and Mollié and Bernardinelli models were used. Results The relative risk of suicide mortality was greater than 1 in 43.0% of Iran's provinces (posterior probability >0.8; range, 0.46 to 3.93). The spatio-temporal model indicated a high risk of suicide in 36.7% of Iran's provinces. In addition, significant upward temporal trends in suicide risk were observed in the provinces of Tehran, Fars, Kermanshah, and Gilan. A significantly decreasing pattern of risk was observed for men (β, −0.013; 95% credible interval [CrI], −0.010 to −0.007), and a stable pattern of risk was observed for women (β, −0.001; 95% CrI, −0.010 to 0.007). A decreasing pattern of suicide risk was observed for those aged 15-29 years (β, −0.006; 95% CrI, −0.010 to −0.0001) and 30-49 years (β, −0.001; 95% CrI, −0.018 to −0.002). The risk was stable for those aged >50 years. Conclusions The highest risk of suicide mortality was observed in Iran's northwestern provinces and among Kurdish women. Although a low risk of suicide mortality was observed in the provinces of Tehran, Fars, and Gilan, the risk in these provinces is increasing rapidly compared to other regions.